Analysis of Pressure Stability on Hydrostatic Test Pressure Control Equipment Using Barton Chart Recorder - Muhammad Fathur Ruhma; Farid Daniel Abizard; Muhammad Yazid Rizky W; Fazal Achmad (Takaza Innovatix Labs Ltd., 2026)
Pressure control equipment is essential for maintaining operational safety and well integrity in oil and gas well operations. This study analyzes pressure stability during hydrostatic testing of lubricator, stuffing box, and pumping tee components at PT. Nesitor workshop, Balikpapan, using a Barton Chart Recorder as the pressure‑monitoring instrument. A qualitative descriptive approach combined with quantitative data analysis was applied based on direct field observation. The research population comprised all pressure control equipment handled by the workshop, while the sample was limited to lubricators, stuffing boxes, and pumping tees instrumented for hydrostatic testing. The Barton Chart Recorder was used as the main instrument, supported by pressure gauges and the Pressure Test System software. Data were analyzed by interpreting pressure‑chart patterns and evaluating pressure stability, holding time, and leak detection. The tests followed API SPEC 6A in three stages: 200 psi for 5 minutes, 5,000 psi for 5 minutes, and 10,000 psi for 15 minutes. The results show that pressure remained stable without any drop in all stages, indicating no leakage and acceptable structural integrity. The conclusion is that standardized API‑based procedures, systematic component identification, and the Barton Chart Recorder provide a reliable basis for evaluating pressure control equipment condition